The Objective and Subjective Caregiving Burden and Caregiving Behaviours of Parents of Adolescents with Anorexia Nervosa. (1st April 2016) - Rhind, Charlotte; Salerno, Laura; Hibbs, Rebecca; Micali, Nadia; Schmidt, Ulrike; Gowers, Simon; Macdonald, Pamela; Goddard, Elizabeth; Todd, Gillian; Tchanturia, Kate; Lo Coco, Gianluca; Treasure, Janet
Abstract: Objective: The study aimed to examine caregiving burden and levels of distress, accommodating behaviours, expressed emotion (EE) and carers' skills, in parents of adolescents with anorexia nervosa. Method: A semi‐structured interview assessed the objective burden (time spent across caregiving tasks) in parents ( n  = 196) of adolescents ( n  = 144) receiving outpatient treatment for anorexia nervosa. Subjective burden (carers' distress), accommodating behaviours, EE and carers' skills were measured by self‐report. Results: Mothers, on average, spent 2.5 h/day of care, mainly providing food and emotional support, compared with 1 h/day by fathers. The level of distress and accommodating behaviour was significantly lower in fathers than in mothers. Accommodating behaviours mediated the relationship between objective burden and subjective burden in mothers, whereas EE and carers' skills did not mediate this relationship for either parent. Discussion: The objective burden for most mothers is high. In order to reduce subjective burden, it may be helpful to target accommodating behaviours. Trial Registration: ISRCTN83003225 ‐ Expert Carers Helping Others (ECHO). Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association